Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ma2025144
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Encumbered Bipyridyl-Derivatized Conjugated Polymers and Metallopolymers Incorporating Phenylenevinylene, Phenyleneethynylene, and Fluorenylene Segments

Abstract: This work reports the preparation of a series of 2,2′-bipyridyl (bipy) modified π-conjugated polymers having an average of one or three monomer units (p-arylene ethynylene for PPE1 and PPE3 or 7,7dihexylfluorene for PF1 and PF3) between metal-binding sites. Spectroscopic data demonstrate that strategic placement of sterically encumbered mesityl groups about the metal binding sites enforces a 1:1 metal to bipy binding ratio. This steric coordination control ensures that the metalated polymers remain solution pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…This has been done with success for a wide range of organic polymers, including CPs such as hyperbranched poly( p ‐phenylene ethynylene)s and some poly( p ‐phenylene vinylene)s in which the conjugation is periodically disrupted by m ‐phenylene units. Derivatives of P1‐I (Chart ) in which the iodo substituent is replaced by small‐molecule chromophores have shown low incidence of interchain interactions while enforcing intrachain interactions between the backbone π ‐system and the small‐molecule chromophore, leading to intramolecular charge transfer and Forster resonance energy transfer (FRET) …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been done with success for a wide range of organic polymers, including CPs such as hyperbranched poly( p ‐phenylene ethynylene)s and some poly( p ‐phenylene vinylene)s in which the conjugation is periodically disrupted by m ‐phenylene units. Derivatives of P1‐I (Chart ) in which the iodo substituent is replaced by small‐molecule chromophores have shown low incidence of interchain interactions while enforcing intrachain interactions between the backbone π ‐system and the small‐molecule chromophore, leading to intramolecular charge transfer and Forster resonance energy transfer (FRET) …”
Section: Introductionmentioning
confidence: 99%
“…Both small molecules (Chart (A)) and polymers (Chart (B)–(D)) have proven useful for fluorescence‐based detection of nitroaromatics . In each of these cases the bulky side chains such as iptycenes (Chart (A) and (B)), cyclophane‐containing ‘canopy’ (Chart (C)) and m ‐terphenyls (Chart (D)) provide free volume around a π ‐conjugated fluorophore for analyte occupancy. Crosslinked conjugated microporous polymer networks likewise provide the free volumes necessary for efficient nitroaromatic entry and detection …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful design and synthesis of these polymers linked by B-O [3][4][5], C-C [6,7], C-N [8], and C=N [9][10][11][12] bonds have been reported. Recent studies have shown that conjugated organic polymers (COPs) with extended π-conjugation possess high thermal stability and structure diversity [13][14][15]. However, the synthesis of these COP materials usually requires expensive precursors and intricate techniques.…”
Section: Introductionmentioning
confidence: 99%